2011
DOI: 10.1590/s1677-04202011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro triacontanol on growth, antioxidant enzymes, and photosynthetic characteristics in Arachis hypogaea L.

Abstract: ABstrACt:In vitro effects of triacontanol (TRIA) on antioxidant enzymes and photosynthetic characteristics were studied in Arachis hypogaea L. cultivars (M-13 and PBS24030). The in vitro impact of TRIA on multiplication potential was also evaluated, which was found to be best at 2.0 ml L -1 TRIA in combination with 6-Benzyl adenine (BA, 3 mg L -1 ) in both the groundnut cultivars. Rhizogenesis was observed in almost all the TRIA treated cultures in both the cultivars. Moreover, shoots failed to set roots, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…In contrast to our findings, the increased total soluble protein has been reported under saline regimes in wheat (Zheng et al, 2009;Farouk, 2011;Barakat et al, 2013;Perveen et al, 2013), Erythrina variegata seedlings (Muthuchelian et al, 2003), green gram (Kumaravelu et al, 2000) and Arachis hypogaea L. (Verma et al, 2011). Similarly, Krishnan and Kumari (2008) also reported TRIA treated soybean plants with improved protein content under saline conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast to our findings, the increased total soluble protein has been reported under saline regimes in wheat (Zheng et al, 2009;Farouk, 2011;Barakat et al, 2013;Perveen et al, 2013), Erythrina variegata seedlings (Muthuchelian et al, 2003), green gram (Kumaravelu et al, 2000) and Arachis hypogaea L. (Verma et al, 2011). Similarly, Krishnan and Kumari (2008) also reported TRIA treated soybean plants with improved protein content under saline conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…NO supplied exogenously provides resistance against stress induced by HMs like Cd in rice (Panda et al 2011) and As in fescue (Jin et al 2010). There is some evidence that the exogenous application of TRIA inhibited lipid peroxidation in spinach and peanut plants' (Ramanarayan et al 2000;Verma et al 2011) leaves and improved membrane integrity by differentially modulating membrane lipid composition (Swamy et al 2009). Perveen et al (2011) found that TRIA-induced improvement in growth might have been due to its effect on the performance of antioxidant enzymes like POD under salt stress (Perveen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S-24; however, foliar-applied TRIA at different growth stages decreased oxidative stress-induced membrane damage, which is apparent from the stressinduced reduction in MDA content (a product of lipid peroxidation) and H 2 O 2 (most stable ROS in plants) in both wheat cultivars. TRIA inhibited lipid peroxidation in spinach (Spinacea oleracea L.) (Ramanarayan et al, 2000) and Arachis hypogaea L. (Verma et al, 2011) leaves and improved membrane integrity by differentially modulating membrane lipid composition (Swamy et al, 2009). In the present study, TRIA-induced improvement in growth might have been due to its effect on the performance of antioxidant enzymes like POD under salt stress Ertani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%